Analisis Financial Distress Bank Perkreditan Rakyat Syariah (BPRS) di Indonesia Periode 2019 - 2020 - Muflihah, Rini (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2022)
This study aims to analyze the financial distress of Islamic Rural Banks (BPRS) in Indonesia in 2019-2020. The research method used is descriptive analysis method, which is a research method by collecting data according to the truth and then the data is compiled, processed and analyzed to be able to provide an overview of the existing problems. The results of this study indicate that Islamic Rural Banks have an indication of financial distress. This is evident from the results of the assessment using the Atlman Z-score method which shows the level of accuracy of the prediction model in 2019 - 2020 is in the gray area or gray area and has the potential for financial distress.